The cost-effectiveness of palivizumab in infants with cystic fibrosis in the Canadian setting: A decision analysis model - Ashleigh A. McGirr; Kevin L. Schwartz; Upton Allen; Melinda Solomon; Beate Sander (Human Vaccines & Immunotherapeutics, 2017)
Background: Children with cystic fibrosis (CF) are at higher risk of severe respiratory syncytial virus (RSV) infection, which can lead to a decline in lung function. A monoclonal antibody, palivizumab (PMB), effectively prevents RSV hospitalizations; however, the high cost of PMB, approximately C$10,000 per patient per RSV season, limits its widespread use. We assess the cost-effectiveness of PMB prophylaxis in CF children less than 2 y of age from the Canadian healthcare payer's perspective. Methods: In 2014, a Markov cohort model of CF disease and infant RSV infections in the Canadian setting was developed based on literature data. Infants were treated with monthly PMB injections over the 5-month RSV season. Lifetime health outcomes, quality-adjusted life years (QALYs) and 2013 $CAD costs, discounted at 5%, were estimated. Findings are summarized as incremental cost-effectiveness ratios (ICERs) and budget impact. Deterministic sensitivity analysis was conducted to assess parameter uncertainty. Results: Implementation of a hypothetical Canadian RSV prophylaxis program resulted in ICERs of C$652,560 (all CF infants) and C$157,332 (high-risk CF infants) per QALY gained and an annual budget impact of C$1,400,000 (all CF infants) and C$285,000 (high-risk CF infants). The analysis was highly sensitive to the probability of severe RSV, the degree of lung deterioration following infection, and the cost of PMB. Conclusions: Our results suggest PMB is not cost-effective in Canada by commonly used thresholds. However, given the rarity of CF and relatively small budget impact, consideration may be given for the selective use of PMB for immunoprophylaxis of RSV in high-risk CF infants on a case-by-case scenario basis.